Study on design and modelling of paper fibre recovery network - Siti Roseha, Mohd Hamzah (2012)
This work presents the development of a Model for Optimal Design for Paper Fibre Networks (MODPFN) applicable for urban case study.This can be achieved by implementing the mathematical approach on design and modelling of paper fibre recovery network.The purposes of this study are to design a mathematical model for paper fibre recovery network and implement the model in an urban case study.This work involved few steps,firstly,extraction of limiting data on paper fibre,followed by representation of superstructure, developing of mathematical formulation and next application of model in GAMS software in order to get optimal maximum fibre recovery and lastly, implemented the model in the urban case study.MODPFN develop can simultaneously target and design of paper fibre recovery network.It is less tedious and more effective compared from previous method from previous researches. The results show that the potential of maximum fresh fibre reduction of 32.48% for high quality paper and 48.66% for low quality paper.